Civil Engineering Materials (Laboratory) Version 2022 - Noorul Hudai Binti Abdullah; Norhayati Ngadiman; Mohd Erwan Sanik; Hazri Mokhtar (Penerbit UTHM, 2022)
The writers of this book as a guideline to understanding of the Civil Engineering Materials (Laboratory) version 2022 for the course DAC 11603 offered by the Centre of Diploma Studies (CeDS), Universiti Tun Hussein Onn Malaysia (UTHM). This book is divided into six (6) experiments; MB01 Vicat Consistency Test to determine the amount of water required for normal consistency according to a specific procedure. MB02 Sieve Analysis of Fine Aggregate experiment to obtain grading curve of fine aggregate. MB03 Sieve Analysis of Coarse Aggregate experiment to obtain grading curve of coarse aggregate. MB04 Workability and Compressive Strength of Concrete experiment to study the workability of the designed mix and compressive strength of concrete cube. MB05 Rebound Hammer Test to check the uniformity of concrete, to determine the properties of the surface of the concrete, and to estimate strength of concrete in structures. MB06 Density, Water Absorption and Compressive Strength of a Brick experiment to determine the density, water absorption, and compressive strength of brick according to the Malaysian standard. Diploma of civil engineering students will benefit from this book.